Embedding a hospital-wide culture of infection control to reduce MRSA bacteraemia rates - Dyas, Anne (International Journal of Infection Control, 2008)
Coping with increasing demands on staff and time and the scrutiny of the Department of Health, the infection control team at Worcestershire Acute Trust reduced the prevalence of methicillin-resistant Staphylococcus aureus and Clostridium difficile by focusing on MRSA screening, environmental cleanliness and antibiotic stewardship. Set with a task of bringing all clinical and managerial staff together, the team got every directorate undertaking its own audit and root cause analysis. The appointment of a new MRSA screening clerk caused an increase in screening compliance to over 90%.